2021
DOI: 10.1002/adhm.202102095
|View full text |Cite
|
Sign up to set email alerts
|

A Nanocoating Co‐Localizing Nitric Oxide and Growth Factor onto Individual Endothelial Cells Reveals Synergistic Effects on Angiogenesis

Abstract: The delivery of nitric oxide (NO)-an intrinsic cellular signaling molecule-is promising for disease treatment, in particular to vascular diseases, due to its endothelial-derived inherent nature. The limited diffusion distance of labile NO prompts researchers to develop various carriers and targeting methods for specific sites. In contrast to the apoptotic effect of NO, such as anticancer, delivering low NO concentration at the desired targeting area is still intricate in a physiological environment. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…NO, a biologically active molecule, can diffuse approximately 100 μm under physiological conditions and penetrate cells. 54 To examine the effective cell penetration of NO, DAF-FM DA, an NO fluorescence probe, was used to evaluate the diffusion of NO in fungal cells. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NO, a biologically active molecule, can diffuse approximately 100 μm under physiological conditions and penetrate cells. 54 To examine the effective cell penetration of NO, DAF-FM DA, an NO fluorescence probe, was used to evaluate the diffusion of NO in fungal cells. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, VEGF was conjugated to VEGFR of ECs surface to enhance cellular functions, such as cell survival, migration, and angiogenesis along with NO. Results suggested that this technique on nanocoating-based NO and VEGF co-localization to cells can be beneficial for vascular development in the field of SCs transplantation and organoid platform [131]. A similar study has showed that the encapsulation of the NO-donor S-nitrosoglutathione (GSNO) into chitosan nanoparticles (CS NPs) overcame NO drawbacks in pharmacological applications, such as, its short half-life.…”
Section: Exogenous Nitric Oxide In Regenerative Medicinementioning
confidence: 96%
“…Since antithrombogenicity is a crucial factor for the long-term success of vascular implants, surface heparinization was further introduced through a stepwise metal (copper)-catechol-(amine) (MCA) surface chemistry strategy. The heparin-grafted and NO-catalytic coating could mimic the physiological functions of native endothelium, which may address the challenges of in-stent restenosis [131].…”
Section: Exogenous Nitric Oxide In Regenerative Medicinementioning
confidence: 99%
“…Therefore, organic nitrates and nitrites have been used as cardiovascular therapeutic agents to improve the dilation of vascular smooth muscle . Indeed, NO not only has been developed for decades for effective cardiovascular disease therapy but also to improve thromboresistance, antirestenosis, and promote re-endothelialization after stent implantation. With active ongoing research on the biological mechanism of NO, scientists will surely report more and more NO nanomedicine candidates for the treatment of a variety of additional diseases …”
Section: Outlook and Summarymentioning
confidence: 99%